A comprehensive review of monkeypox virus and mpox characteristics - Alakunle, Emmanuel; Kolawole, Daniel; Diaz-Cánova, Diana; Alele, Faith; Adegboye, Oyelola; Moens, Ugo; Okeke, Malachy Ifeanyi (Frontiers in Cellular and Infection Microbiology, 2024)
Monkeypox virus (MPXV) is the etiological agent of monkeypox (mpox), a zoonotic disease. MPXV is endemic in the forested regions of West and Central Africa, but the virus has recently spread globally, causing outbreaks in multiple non-endemic countries. In this paper, we review the characteristics of the virus, including its ecology, genomics, infection biology, and evolution. We estimate by phylogenomic molecular clock that the B.1 lineage responsible for the 2022 mpox outbreaks has been in circulation since 2016. We interrogate the host-virus interactions that modulate the virus infection biology, signal transduction, pathogenesis, and host immune responses. We highlight the changing pathophysiology and epidemiology of MPXV and summarize recent advances in the prevention and treatment of mpox. In addition, this review identifies knowledge gaps with respect to the virus and the disease, suggests future research directions to address the knowledge gaps, and proposes a One Health approach as an effective strategy to prevent current and future epidemics of mpox.